Persepsi Gen Z Terhadap Konten Viral Tiktok @bogoraquagame Dalam Meningkatkan Brand Awareness: Gen Z's Perception of Viral TikTok Content @bogoraquagame in Increasing Brand Awareness - Fadia, Nur Anisah; Priatna, Wahyu Budi; Dharmawan, Leonard (DAS Institute, 2025)
This research aims to analyze Generation Z’s perception of viral TikTok content on @BogorAquaGame and its relationship with brand awareness. The study employs a quantitative approach using a survey method with data collected from 33 respondents, all of whom are students of the Digital Communication and Media Study Program, IPB University, representing the Gen Z demographic and active TikTok users. The data were gathered through a closed-ended questionnaire based on Likert scale 1–4 and analyzed using SPSS with validity, reliability, and Spearman’s Rho correlation tests. The results indicate that all instrument items are valid and reliable, with a Cronbach’s Alpha value of 0.908, signifying strong internal consistency. Furthermore, the Spearman correlation value of 0.927 (Sig. = 0.000) demonstrates a very strong and significant relationship between viral content perception and brand awareness. These findings confirm that creative, relevant, and authentic TikTok content can effectively enhance brand recognition and recall among Gen Z audiences. The study implies that local creators and businesses should strategically utilize viral marketing to strengthen brand positioning through culturally resonant content. However, the research is limited by a small sample size and focus on a single account, suggesting the need for broader future studies involving diverse social media platforms and audiences.